THE ROLE OF DCM4CHEE AS AN OPEN SOURCE PACS IN THE RADIOLOGY DEPARTMENT OF PRIMAYA HOSPITAL SEMARANG - Nuha, M. Dzawin; Wibowo, Gatot Murti; Setjadiningra, Rr. Lydia Purna Widyastuti; Saputra, Kurniawan; Puspita, Mega Indah; Pranandya, Brian Ilham (Postgraduate Program , Poltekkes Kemenkes Semarang, 2024)
This research explores the potential use of DCM4CHEE as an open-source Picture Archiving and Communication System (PACS) that is highly flexible for development in the current era. Despite being open source, DCM4CHEE has proven to be effective and reliable in healthcare settings, particularly in radiology department. Primaya Hospital Semarang has successfully implemented DCM4CHEE as an integrated archive system directly connected to CT Scan and Conventional X-Ray modalities. Direct observations were conducted over a significant period at the radiology installation of Primaya Hospital Semarang, which utilizes DCM4CHEE. This provided direct insights into how the system is implemented and used in practical situations. Furthermore, in-depth interviews were conducted with radiographers to gain their perspective on the experience of using DCM4CHEE. The research results indicate that the use of DCM4CHEE contributes positively in various aspects, including user-friendly operation, adequate utility, workflow improvement, and cost savings in healthcare services. The implementation of this software not only aids in the efficient management of radiological data but also reduces dependence on traditional filming systems, supporting the transition towards a paperless workflow. In conclusion, DCM4CHEE is reliable and highly beneficial in the context of healthcare services. Its adaptability allows seamless integration with Hospital Information Systems (HIS) and Radiology Information Systems (RIS), enhancing overall interoperability and efficiency. This research provides a foundation for recommending the use of DCM4CHEE as a customizable PACS solution that can positively contribute to improving the quality of radiology services in various healthcare department.